2008
DOI: 10.1002/dvdy.21685
|View full text |Cite
|
Sign up to set email alerts
|

Integrin‐linked kinase regulates E‐cadherin expression through PARP‐1

Abstract: Repression of E-cadherin expression by the transcription factor, Snail, is implicated in epithelial to mesenchymal transition and cancer progression. We show here that Integrin-Linked Kinase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 59 publications
1
63
0
1
Order By: Relevance
“…Likewise, PARP-1 was identified as a SIRE-binding protein. ILK silencing inhibited PARP-1 binding to SIRE, and PARP-1 silencing decreased both Zeb1 and Snail, which resulted in the upregulation of E-cadherin (35). Vimentin, the intermediate filament protein, is an important marker of the EMT and a requisite regulator of mesenchymal cell migration (36).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, PARP-1 was identified as a SIRE-binding protein. ILK silencing inhibited PARP-1 binding to SIRE, and PARP-1 silencing decreased both Zeb1 and Snail, which resulted in the upregulation of E-cadherin (35). Vimentin, the intermediate filament protein, is an important marker of the EMT and a requisite regulator of mesenchymal cell migration (36).…”
Section: Discussionmentioning
confidence: 99%
“…Previously it has been reported that ILK-dependent activation of Snail1 transcription required PARP-1 binding to ILK promoter (McPhee et al, 2008). To analyze the involvement of ILK in the interaction between PARP-1 and Snail1, ILK was knocked down using siRNA (Figure 4h).…”
Section: Snail1 Protein Is Polyadp-ribosylatedmentioning
confidence: 99%
“…Recently it has been demonstrated that poly(ADP-ribose) polymerase-1 (PARP-1) is involved in the activation of Snail1 gene transcription through binding to the integrin-linked kinase (ILK) promoter (McPhee et al, 2008). PARP-1 is the principal member of a family of enzymes with poly(ADP-ribosyl)ation catalytic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Given that both Cten and integrinlinked kinase (ILK) seem to regulate cell motility and downregulate E-cadherin (Somasiri et al, 2001;Oloumi et al, 2004;McPhee et al, 2008), we hypothesised that Cten may signal through ILK. In addition, we evaluated the prognostic significance of Cten in a series of CRC and we used an in vivo model to test whether Cten could influence tumour metastasis.…”
Section: Introductionmentioning
confidence: 99%